Investigating the effect of pH on cellulase enzyme efficiency on the OCC pulp properties - Ghasem Asadpour (Regional Information Center for Science and Technology (RICeST), 2018)
The purpose of this study is to investigate the effect of pH on cellulase enzyme activity on the drainage and strength properties of OCC pulp. Recycled OCC pulp was pretreated with consistency 0.4 percent, in constant condition the temperature is 50˚C, duration 1 hour and range pH:4-4.5, 8-8.5 with cellulase enzyme at three levels 0.1, 0.3 and 0.5 percent (according to paper pulp dry weight). The results showed that pretreatment of cellulase enhances the freeness of pulp in comparison with the control samples, but by increasing the concentration of enzyme, the freeness of pulp was reduced in pH:4-4.5 the highest freeness is at the level of 0.1 percent and in pH:8-8.5 at the level of 0.3 percent. Also, papers were evaluated for resistance properties. The results showed that the increase in the use of cellulase enzyme has increased the tensile and burst strength index. As, in the alkaline pH, the effect of the cellulase enzyme on the increase of these strength was higher than the acid pH. The OCC pulp strength tear index, only in low levels of cellulase enzyme and in acidic pH, increased strength was observed, but with increasing enzyme consumption, there was a decrease in tear strength. Also, for strength to crushing, there was no specific trend regarding the amount of enzyme and pH on enzyme function.